Tracking Adults’ Eye Movements to Study Text Comprehension: A Review Article - Georgia Andreou; Maria Gkantaki (Languages)
Adult readers’ cognitive effort during text processing is often associated with their reading comprehension, learning ability, and achievement scores. The aim of this review is to examine and analyze the current literature on the use of eye tracking technology as a tool for assessing text comprehension. A systematic review was conducted and, after the final screening, 13 articles were analyzed that fell into three main areas: (a) eye movements during reading in print and digital media, (b) eye tracking in text comprehension with perspective effects, and (c) eye tracking in text comprehension with instructional strategy effects. The findings of this review showed that during reading, the amount of cognitive effort invested in text processing, whether induced by the text, the task, or the readers themselves, is usually reflected in longer total fixation times, both as a result of higher fixation frequencies and longer fixation durations.